IMPLEMENTASI ARTIFICIAL INTELLIGENCE MELALUI SPEECH-TO-TEXT SEBAGAI ALAT BANTU TUNARUNGU BERKOMUNIKASI - Firdaus, Efrans (JUTECH : Journal Education and Technology, 2024)
As a reason for research based on the author's interview with one of the Special Assistant Teachers (GPK) of SLB B Tunas Harapan Karawang on Friday, November 10 2023, it was said that Deaf students experienced several obstacles in the areas of socialization, social interaction, communication and cooperation because they were still minimal in vocabulary, Difficulty interpreting words or sentences that contain figurative meaning, and Difficulty interpreting abstract words. The aim of the research is to make things easier when individuals experience limitations in communication, in this case they have problems with hearing abilities or are deaf, which creates their own obstacles to carrying out the social interaction process. The research method or approach based on previous researchers carried out on the ASL language translation system is that it is able to display letters resulting from data processing in the system onto an LCD contained in the 1Sheeld application. The research results are to find out the implementation of Speech-to-Text Software, how to initialize and record sound, testing variations in speaking speed, configuring the Speech-to-Text program with Raspberry Pi, testing the Speech-to-Text system, and implementing hardware in the Speech-to-Text subsystem. The conclusion of this research is to answer the problems faced by Deaf students at SLB B Tunas Harapan Karawang in communicating with normal people.